2013
DOI: 10.3201/eid1904.120380
|View full text |Cite
|
Sign up to set email alerts
|

Response to a Rabies Epidemic, Bali, Indonesia, 2008–2011

Abstract: Emergency vaccinations and culling failed to contain an outbreak of rabies in Bali, Indonesia, during 2008–2009. Subsequent island-wide mass vaccination (reaching 70% coverage, >200,000 dogs) led to substantial declines in rabies incidence and spread. However, the incidence of dog bites remains high, and repeat campaigns are necessary to eliminate rabies in Bali.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 4 publications
(3 reference statements)
3
117
0
1
Order By: Relevance
“…In 2008, however, an incursion occurred, and the disease spread rapidly across the island. The resulting epidemic led to over 100 human rabies deaths (8) and thousands of human exposures requiring expensive postexposure prophylaxis (9). Local, national, and international pressure led to concerted efforts to control the disease, largely based on mass vaccination of dogs, but also including culling of dogs by local authorities, as described by Putra et al (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, however, an incursion occurred, and the disease spread rapidly across the island. The resulting epidemic led to over 100 human rabies deaths (8) and thousands of human exposures requiring expensive postexposure prophylaxis (9). Local, national, and international pressure led to concerted efforts to control the disease, largely based on mass vaccination of dogs, but also including culling of dogs by local authorities, as described by Putra et al (9).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting epidemic led to over 100 human rabies deaths (8) and thousands of human exposures requiring expensive postexposure prophylaxis (9). Local, national, and international pressure led to concerted efforts to control the disease, largely based on mass vaccination of dogs, but also including culling of dogs by local authorities, as described by Putra et al (9). The first dog vaccination campaign was conducted from October 2010 to March 2011, followed by the second campaign in April through June 2011, and third campaign in March to June 2012 (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Even in wildlife-rich areas in Africa, dogs act as maintenance hosts and reservoirs for canine rabies (Lembo and others 2008), and vaccination of 70 per cent of the dog population is sufficient to disrupt transmission cycles and eliminate the disease, not only in domestic dogs, but in all other mammalian hosts (Hampson and others 2009), with corresponding declines in rabies exposures in people (Cleaveland and others 2003). Operational research has demonstrated that, even where most dogs are free-roaming, as is the case in most communities in Africa and Asia, it is feasible to implement campaigns that achieve 70 per cent vaccination coverage (Kayali and others 2003, Kaare and others 2009, Davlin and Vonville 2012, Putra and others 2013). Dog vaccination campaigns are also likely to be more cost-effective for preventing human rabies deaths than relying on human PEP alone, and over five- to 10-year horizons have the potential to result in net economic benefits (Bögel and Meslin 1990, Zinsstag and others 2009, Tenzin and others 2012, Fitzpatrick and others 2014).…”
Section: The Global Rabies Problemmentioning
confidence: 99%
“…Less than 11% of the dog population has been identified as ownerless in Zimbabwe, Chad, Tanzania, and South Africa (15). In densely populated Asian settings, where community dogs are common, techniques for vaccinating free-roaming dogs have been successfully applied (11).…”
Section: Elimination Is Achievablementioning
confidence: 99%